Performance of Technical Supervision and Its Evaluation on Transport Constructions - Petr Suchánek; Zdeněk Dufek (Civil Engineering Journal, 2023)
The aim and purpose of the research are to analyze the performance of the technical supervision of the investor within the Czech construction industry during the construction, particularly focused on transport line structures. It is about clarifying the meaning and role of technical supervision in the public sector in transportation structures. In the first phase, a literature search is carried out on the current state of performance of the technical survey, and its work content is determined, including the method of its evaluation within the framework of a public contract. On the basis of these conclusions, a questionnaire is designed, which determines the real time-consuming activities during the performance of supervision and, at the same time, examines the tools used in its performance. Conclusions from the questionnaire research are examined, and steps for possible streamlining are proposed. As part of the examination of the proper evaluation of performance, a more suitable model of evaluation of these services is sought based on the previous analysis of the time-consuming nature of the technical supervision activity and according to the existing evaluation methods. Doi: 10.28991/CEJ-2023-09-03-013 Full Text: PDF